Biography of James Hudson Taylor - Taylor, Howard (Hodder Christian paperbacks., 1973)
A biography of the famous missionary, James Hudson Taylor. His unbreakable faith in God during a life dedicated to reaching China's millions with the Gospel has been a lasting inspiration to many.